Pemaknaan Artefak Budaya dan Tuturan Perayaan Keagamaan - Turnomo Rahardjo; Hapsari Dwiningtyas Sulistyani; Lintang Ratri Rahmiaji (Jurnal Komunikasi, 2022)
This study was intended to comprehend how faith-based community groups communicated about cultural artifacts such as diverse Christmas celebration speeches. this study employed a phenomenological approach in order to understand the importance of identity expressions from the cultural artifacts associated with the Christmas season. This study found that faith-based community organizations interpret the issues of Christmas speeches or greetings differently. Muhammadiyah "frees" its adherents to wish Christians a Merry Christmas or not. Additionally, since Christmas characteristics were seen as examples of cultural inventiveness, it did not raise any objections to them. Congratulating the religious holidays of other religions, such as "Merry Christmas," are officially not prohibited by Nahdlatul Ulama. Similar circumstances apply to the Indonesian Chinese Islamic Association. With so many different religions practiced in Chinese society, sending presents and expressing congratulations during religious events is customary. Persatuan Islam and Majelis Mujahidin offered a different viewpoint. Because it goes against their beliefs, they generally resist sending christmas greetings.